2016
DOI: 10.21037/apm.2016.05.03
|View full text |Cite
|
Sign up to set email alerts
|

Community-based participatory research: understanding a promising approach to addressing knowledge gaps in palliative care

Abstract: Concern over the need for effective and accessible healthcare for individuals with advanced chronic illness has drawn attention to the significant gaps in our knowledge of palliative medicine. To advance our understanding of this field, community-based participatory research (CBPR) is proposed as a tool for future research initiatives. This paper offers a rationale for how CBPR may be employed to address specific gaps in palliative care research. Several examples where this approach has been used previously ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 29 publications
0
42
0
Order By: Relevance
“…Particular approaches, notably Participatory Action Research, Community Based Participatory Research and emancipatory research, were suggested as being effective in promoting involvement. 6972 These approaches used principles of equity, power-sharing and reciprocal transfer of knowledge and skills. 49,55,73 However, the evidence was limited because they had not been widely or comprehensively used.…”
Section: Resultsmentioning
confidence: 99%
“…Particular approaches, notably Participatory Action Research, Community Based Participatory Research and emancipatory research, were suggested as being effective in promoting involvement. 6972 These approaches used principles of equity, power-sharing and reciprocal transfer of knowledge and skills. 49,55,73 However, the evidence was limited because they had not been widely or comprehensively used.…”
Section: Resultsmentioning
confidence: 99%
“…CBPR has been recommended as a promising strategy for PC research that aligns with the priorities of stakeholders, as a means to deliver tailored and appropriate care to underserved communities. 66 Phase 1 engaged community members in the planning phase, serving as the first step in forming relationships and building trust with the community, and in obtaining community guidance into the study. Community Advisory Group (CAG) members were recruited with the assistance of the community health educator at BMH who had strong ties with community groups.…”
Section: Methodsmentioning
confidence: 99%
“…According to Israel et al (), the use of CBPA is relevant in the humanities, medicine, public health, and social sciences (Riffin et al, , p. 219). Additionally, the concept is used interchangeably with “community involved,” “collaborative,” “participatory,” or “community‐centred” approaches (Riffin et al, ). A fundamental characteristic of CBPA is the wilful engagement with community members and the sharing of unique local perspectives and local knowledge in community transformation and sustainability.…”
Section: The Philosophy Of Community Economic Development Local Econmentioning
confidence: 99%